Usefulness of soluble urokinase plasminogen activator receptor (suPAR) as an inflammatory biomarker in obese children. (1st February 2017) - Kosecik, Mustafa; Dervisoglu, Pinar; Koroglu, Mehmet; Isguven, Pinar; Elmas, Bahri; Demiray, Tayfur; Altindis, Mustafa
Abstract: Objective: Soluble urokinase plasminogen activator receptor (suPAR) has emerged as a relatively new biomarker that reflects increased inflammatory status and been associated with cardiovascular risk. We wanted to investigate the predictive value and usefulness of suPAR as an inflammatory biomarker in obese children. Methods and results: Of the total 136 participants, 76 (36 male, 40 female) were in obese group and 60 (24 male, 36 female) were in control group. The median age was 12.05 (6.16–17.30) years old for obese group, and 12.83 (8.00–16.75) years old for control group. Obese children had statistically significantly higher heart rate, systolic and diastolic blood pressure, EAT and LV mass than control group ( p  < 0.01). The median suPAR level in obese group was not statistically different than in control group (0.54 vs. 0.59, p  = 0.26). The median hsCRP level in obese group was found statistically significantly higher than in control group (1.97 vs. 0.41, p  < 0.01). A significant positive correlation between hsCRP and BMI in the obese participants was found (r = 0.45, p  < 0.01), but not a relationship between suPAR and BMI (r = − 0.21, p  > 0.05). Conclusion: Our research did not demonstrate the usefulness of suPAR as an inflammatory biomarker and a predictive value for future atherosclerosis in obese children. Further studies with larger sample size are required to determine whether suPAR is useful as an inflammatory biomarker in childhood obesity.